2010
DOI: 10.1080/15398281003780966
|View full text |Cite
|
Sign up to set email alerts
|

A MedlinePlus® Kiosk Promoting Health Literacy

Abstract: As an ongoing community outreach project, a pictorial touch-screen kiosk and Web site was developed for 48 MedlinePlus® tutorials. This learning experience serves Davidson County, Tennessee’s uninsured patients at the University of Tennessee/Baptist Hospital’s Internal Medicine Clinic. The availability of a health information kiosk at the University of Tennessee/Baptist Hospital primary care clinic significantly increases health literacy for patients by providing reliable, physician-recommended information in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 13 publications
1
34
0
7
Order By: Relevance
“…Four of the interventions were not theoretically grounded. [32][33][34]39 Interventions that were theoretically grounded all used some type of decision-oriented health behavior theory. Due to the diversity of the interventions and the scope of this analysis, it is not feasible to comparatively assess whether having a theoretical foundation made a difference in outcomes.…”
Section: General Characteristics Of the Interventionsmentioning
confidence: 99%
“…Four of the interventions were not theoretically grounded. [32][33][34]39 Interventions that were theoretically grounded all used some type of decision-oriented health behavior theory. Due to the diversity of the interventions and the scope of this analysis, it is not feasible to comparatively assess whether having a theoretical foundation made a difference in outcomes.…”
Section: General Characteristics Of the Interventionsmentioning
confidence: 99%
“…They found that people visited the kiosk, but did not complete interviews. 20 In the model demonstrated, a health professional assists the patient in navigating the site and responds to patient questions. Pharmacy students acting as research assistants drew on their training in medications and patient education and interacted with patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 Kiosks can deliver audio-visual material such as interactive tutorials, as was done by Teolis in her 2010 study of low-income, low-literacy patients in Tennessee. 20 In this study, the kiosk was used to increase patients' understanding of their health.…”
Section: Kiosksmentioning
confidence: 99%
“…IPC tools are more preferred choice therefore we used "human" interface as one of the key strategy in our kiosk, both at facility and community [7]. [14]. Our experience shows that the services at community kiosk need to be designed as per the needs of catchment population for kiosk model to be effective [19].…”
Section: Discussionmentioning
confidence: 99%